The academic supervision in improving the pedagogical competence of teachers - Muhammad Yani; Murniati AR; Nasir Usman (STAI Hubbulwathan Duri, 2022)
This study aimed to examine teachers' abilities in organizing, implementing and overcoming obstacles to implementing academic supervision programs to enhance their pedagogical competence. Using observation, interviews, and documentation studies, qualitative methods, and data gathering approaches were utilized for data collection. The subjects of the study were the principals of three high schools in Aceh and the biology professors from each school. The results demonstrated that the planning was developed through conversation with the teacher to identify problems, implementation approaches, and clinical supervision implementers. The program implementation plan incorporates all Education Office personnel, managers, and school principals. However, many teachers still do not understand academic supervision, both in terms of how it is implemented and its function, and there is a lack of supervisors to solve academic supervision problems. However, the implementation of academic supervision is facilitated by the high willingness of teachers to carry out academic supervision and their strong support from the Department of Education